Efeito do treino com exergames no desempenho cognitivo e funcional de idosos sem demência - Carneiro , Miriam Lúcia da Nóbrega (2015)
The population aging is a universal phenomenon and this causes an increasing concern with this population and the increase in the life expectancy. In regards to the elderly, the physical exercises are essential, therefore they assist in the prevention of the illnesses caused by aging and in the promotion of its independence and quality of life. This research had the general objective to analyze the effect of the Exergames in the cognitive performance (attention and memory) and functionary (balance, marches, daily force of the inferior members and activities) of elderly without dementia. One was about an almost experimental and quantitative research with accomplishment of daily pre-test and after-test, carried through before and after intervention of psychomotor protocol set of rules with Exergames. The final sample of 18 elderly was equally divided between experimental group and control. At an assisted living facility for elderly individuals, located in Joao Pessoa, thirty sessions of exercises utilizing theX-BOX 360 Kinect® and Nitendo Wii® consoles were carried through with a frequency of three times a week and one hour of duration a day. To evaluate the effect of the intervention, functional cognitive instruments were applied to the elderly participants. The data had been analyzed statistically through inferential tests of comparison of averages and the level of significance adopted in this research was of 5%. In the results it was observed in the comparison between the groups (intervention x controlled) that the training with Exergames contributed significantly for the improvement of the functional performance (p = 0.001) and of the activities of daily life (p = 0,015). In the cognitive performance, significant improvement in the general cognition was observed, through the Moca, in the group of intervention (p = 0,007) and in the immediate logical memory (p = 0.001) and delayed (p = 0,038) between the groups. Due to the preliminary results of this research, it is concluded that the Exergames work as a new strategy in health with the purpose to provide improvement and/or cognitive function maintenance in the elderly, promoting a healthy aging and contributing for the satisfaction with the practice of physical exercise.